2014
DOI: 10.1002/jor.22729
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the tissue effects of tribo‐corrosion: Uptake, distribution, and speciation of cobalt and chromium in human bone cells

Abstract: Cobalt and chromium species are released in the local tissues as a result of tribo-corrosion, and affect bone cell survival and function. However we have little understanding of the mechanisms of cellular entry, intracellular distribution, and speciation of the metals that result in impaired bone health. Here we used synchrotron based X-ray fluorescence (XRF), X-ray absorption spectroscopy (XAS), and fluorescent-probing approaches of candidate receptors P2X7R and divalent metal transporter-1 (DMT-1), to better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
2
14
1
Order By: Relevance
“…Indeed, Cr(VI) K-Edge spectrum exhibits a typical pre-edge feature in the XANES region. The absence of such feature and the strict resemblance with Cr(III) spectrum were consistent with the intracellular bio-reduction model of Cr(VI) [51].…”
Section: Speciation Of Toxic Elementssupporting
confidence: 84%
See 1 more Smart Citation
“…Indeed, Cr(VI) K-Edge spectrum exhibits a typical pre-edge feature in the XANES region. The absence of such feature and the strict resemblance with Cr(III) spectrum were consistent with the intracellular bio-reduction model of Cr(VI) [51].…”
Section: Speciation Of Toxic Elementssupporting
confidence: 84%
“…The study of inorganic compounds effects on human health is one of oldest branch of applied toxicology. Modern orthopedics offers interesting XAS case studies [49][50][51]. Cobalt, chromium and relative alloys are the typical constituents of hips prosthesis but also the main responsible for hips failure and induced toxicity.…”
Section: Speciation Of Toxic Elementsmentioning
confidence: 99%
“…The lack of any effect of Cr 3+ alone is consistent with the observations of Kanaji and coworkers and the previously held dogma of the relative inability of Cr 3+ to cross cell‐membranes 34. In contrast to this dogma, we have previously shown the intracellular localization of Cr 3+ in osteoblasts,21 as well as an additive effect of Co 2+ and Cr 3+ treatment 22. Thus the increased effect of combined ions at 500 μg/L over the effect of Co 2+ alone observed in this study suggests for the first time potential facilitation of Cr 3+ entry into osteocytes, as well as common downstream signaling.…”
Section: Discussioncontrasting
confidence: 94%
“…Periprosthetic concentrations are several fold higher (median Co, 113 μg/L; median Cr, 54 μg/L),18 while patients with failing prosthesis have reported Co and Cr concentrations as high as 528 μg/L (range: 0–13,000 μg/L) and 1,844 μg/L (range: 0–38,600 μg/L), respectively 19. We recently demonstrated that exposure to Co 2+ and Cr 3+ adversely affects both osteoclast and osteoblast survival and function, including the mineralization of prosthesis surfaces in vitro, at concentrations equivalent to those found clinically 20, 21, 22…”
mentioning
confidence: 92%
See 1 more Smart Citation